Desenvolvimento de formulação cosmética contendo carreadores lipídicos nanoestruturados à base de manteiga de Ourateasp. : uma estratégia nanotecnológica para o aumento da hidratação cutânea - Galvão, Juliana Gouveia (2015)
Nanostructured lipid carriers (NLCs) have been developed in order to improve cutaneous hydration. Due to its ultrafine particle size it is possible a film formation on the skin which decreases transepidermal water loss, improving occlusive effect and hydration. In this context, the aim of this work was to develop a formulation containing NLCs based in Ouratea sp. butter (Ochnaceae) as a strategy to increase cutaneous hydration. Firstly, it was performed a characterization of the components such as, stearic acid (SA), Ouratea sp. butter (OB), Phospholipon 90G®, and its physical mixtures by Differential Scanning Calorimetry (DSC), Thermogravimetry (TG) and X ray Diffraction (XRD). The NLCs were prepared using the diffusion solvent method and evaluated for particle size, polidispersity index, zeta potential, pH and conductivity. Moreover, NLCs were characterized by DSC, XRD and Transmission electron microscopy (TEM). Finally, the NLCs were incorporated into a cream base and were evaluated for rheological behavior, occlusive effect and potential cutaneous hydration in vitro. From the raw materials characterization was possible to observe in which the PM1 (SA + OB) 1:1 showed a slightly shift of the melting point corresponding to SA (57 to 50°C) and presented an amorphous portion at ~ 20° in the XRD analysis. These observations could be attributed to a decrease of crystallinity when compared with solid lipid pure, highly ordered. With the addition of Phospholipon® 90G (PM2), the melting point was highly shifted to lower temperature (57 to 34°C), and presented a pronounced amorphous at ~ 20° in XRD. Since the NLCs need to remain solid at room and body temperature, it is suggested that using a lower proportion of the Phospholipon® 90G in NLCs formulations. From the CMC determination of SDS surfactant (8,02 mmol L-1) was possible to suggest a range concentration of the SDS in the NLCs preparations. The formulation with the highest SDS concentration (24 mmol L-1) demonstrated the lowest size particle (~ 240 nm), however there were no difference in the zeta potential over formulation that using 10 mmol L-1 of SDS (~ -50 mV). The NLCs presented a decrease in the enthalpy (ΔHNLC8 = 22.2, ΔHNLC10 = 23.2, ΔHNLC24 = 7.2 J/g) and also an increase in the width peak when compared with solid lipid SA pure (ΔHSA = 164.1). In addition, the XRD analysis demonstrated that NLCs presented main peaks both formulations are similar to those found in the SA (23.93°, 25.09°, 27.98°), but with a lower intensity. These observations suggest a lipid matrix less ordered which result in NLC formation. TEM results confirmed previous data related to NLCs particle size (200 to 300 nm). After the incorporation of the NLC10 into a cream base, it was possible to observe an increase in the occlusive effect and potential cutaneous hydration. Therefore, NLCs containing Ouratea sp. butter can be an attractive nanotechnology way to increase cutaneous hydration.